UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE PADA TEMA TEMPAT TINGGALKU DI KELAS IV SD NEGERI 068003 TAHUN PEMBELAJARAN 2018/2019 - SITUMORANG, SARI NAULI (Unversitas Katolik Santo Thomas, 2019)
This type of research is class action research (PTK). This research aims to improve students ' learning outcomes by using the Inside Outside Circle theme of my residence in the sub I'm proud of my place to stay class IV Elementary school 068003 Medan Year learning 2018/2019. The subject in this study was a grade IV student of SD Negeri 068003 Medan which numbered 22 people consisting of 12 male students and 10 female students. The study consists of two cycles namely cycle I and cycle II. Each cycle consists of a one-time meeting. To obtain data during the study post-test used twice in two cycles to determine the increase in student learning outcomes and the teacher activity observation sheet to determine the effectiveness of models used by teachers and sheets Students to learn the extent to which students can apply a learning model that is conceived in the learning process.The results showed that by using the Inside Outside Circle model in Cycle 1, the average student learning results were 64.54% or about 54.55% of students who completed the results of 12 students. The results on this I cycle have not yet reached the expected outcome level. It is done cycle II and the average value of student learning outcomes is 81.27% with a percentage of 90.90% of students who have completed a total value of 20 students. Thus there is an increase in student learning outcomes of 90.90%. Based on the results of the data obtained, it can be concluded that the use of the Inside Outside Circle model can improve the learning outcomes of grade IV students of elementary School 068003 Medan year of learning 2018/2019.